Tenofovir disoproxil fumarate in the treatment of chronic hepatitis B. (August 2012) - Buti, Maria; Homs, Maria
The specific drugs available for chronic hepatitis B infection include standard and pegylated IFN-α, and nucleoside/nucleotide analogs that directly inhibit the reverse transcriptase. The main goal of current hepatitis B virus therapy is to achieve sustained suppression of viral replication to prevent the development of chronic liver disease, but favorable long-term tolerability and resistance profiles are also desirable. This article reviews the chemistry and the mechanisms of action of tenofovir disoproxil fumarate, but it also focuses on the related clinical trails designed to date, in which clinical efficacy has been analyzed attending to HBe antigen status. In addition, studies including patients that have been previously treated with lamivudine or adefovir are discussed.